Aceria tulipae - Cilbircioğlu, Cihan; Çobanoğlu, Sultan (Zenodo, 2019)
Aceria tulipae (Keifer, 1938) Specimens examined Taşköprü / Tekev-Karşı Village garlic storage. 8.VII.2015 (2 ♀♀, 2 ♂♂); Taşköprü / Akdoğan Tekke Village garlic storage. 30.VIII.2015 (5 ♀♀, 1 ♂); Hanönü / Kornapa Village. 28.IV.2016 (1 ♀, 1 ♂); Taşköprü / Alisaray Village. 28.IV.2016 (1 ♀). Comments Members of A. tulipae feed on young leaves and are found in layers of tulips, onions and garlic bulbs. As a result of their feeding on knitting, twisting, curling green parts and leaves of the plants, they damage and dry the leaf texture (Debnath and Karmakar 2013). This species carries the wheat streak mosaic virus (WSMV) and garlic mosaic virus especially in garlic and onions which cause significant yield losses in the economic sense (Denizhan 2012). Denizhan (2012) reported this mite feeding on the leaves of garlic. This species was found in nine garlic storages of Taşköprü and Hanönü in this study.

{"references": ["Debnath, P. & Karmakar, K. (2013) Garlic mite, Aceria tulipae (Keifer) (Acari: Eriophyoidea) - a threat for garlic in West Bengal, India. International Journal of Acarology, 39 (2): 89 - 96.", "Denizhan, E. (2012) Turkiye eriophyoid faunasi icin yeni bir kayit: Aceria tulipae (Keifer, 1938) (Acarina: Eriophyoidea). Bitki Koruma Bulteni, 52 (1): 119 - 122."]}

Published as part of Cilbircioğlu, Cihan & Çobanoğlu, Sultan, 2019, Phytophagous mite (Acari) species on garlic (Allium sativum L.) cultivation areas and storages of Kastamonu, Turkey, pp. 211-224 in Persian Journal of Acarology 8 (3) on page 220, DOI: 10.22073/pja.v8i3.46349, http://zenodo.org/record/7173998
Keywords: Arthropoda; Aceria; Arachnida; Animalia; Trombidiformes; Biodiversity; Eriophyidae; Aceria tulipae; Taxonomy; 2. Zero hunger; 3. Good health